Relationship between the membrane inhibitor of reactive lysis and the erythrocyte phenotypes of paroxysmal nocturnal hemoglobinuria. - Holguin, M H (1989)
Susceptibility to hemolysis initiated by activated cobra venom factor (CoF) complexes is a characteristic that distinguishes the most complement-sensitive type III erythrocytes of paroxysmal nocturnal hemoglobinuria (PNH) from the intermediately sensitive type II and the normally sensitive type I cells. Recently we isolated a membrane constituent from normal erythrocytes that inhibits CoFBb-initiated hemolysis, and this protein was designated membrane inhibitor of reactive lysis (MIRL). To investigate the molecular basis of the variability in complement sensitivity among PNH erythrocytes, the surface expression of MIRL and decay accelerating factor (DAF) on the three phenotypes of PNH was quantified immunochemically. Both complement regulatory proteins were markedly deficient on the erythrocytes from a patient with predominately type III cells. The erythrocytes from patients with a majority of either type II or I cells were also significantly deficient in both MIRL and DAF. While cytofluorometric analysis confirmed the quantitative deficiencies, segregation of erythrocytes into discrete subpopulations that expressed either no MIRL or normal amounts of MIRL was not observed. The results of immunoprecipitation studies were consistent with quantitative, but not qualitative abnormalities of MIRL and DAF. Selective removal of the sensitive erythrocytes indicated that approximately 20% of the normal amount of MIRL is sufficient to protect cells from CoF-initiated lysis. These studies suggest that relatively subtle quantitative differences in membrane complement regulatory proteins underlie the variability in complement sensitivity of PNH erythrocytes.